Toughened double-silver LOW-E coated glass and preparation method thereof
By plating a composite layer on the double silver low-radiation coating glass, including a combination of multiple AZO, NiCr, Ag and other materials, and setting an intermediate dielectric layer to change the propagation path of light, the large color difference in the glass surface of the double silver product is solved. The problem of visual consistency and cost reduction effect.
Patent Information
- Application Number
- CN202411499287.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
AI Technical Summary
When double silver low-radiation coating glass is observed at different angles, the color of the glass surface will change significantly, resulting in poor visual consistency and design limitations, which will affect the aesthetics of the building.
Using a temperable double silver LOW-E coated glass, an intermediate dielectric layer is arranged to change the propagation path of light by plating a composite layer on the glass substrate, including a combination of multiple layers of AZO, NiCr, Ag and other materials, and a combination of materials such as AZO, NiCr, and Ag, to weaken the optical drying. Refractive effect involved.
It effectively reduces the color difference between glass surfaces when viewed at different angles, achieves visual consistency, and solves the problem of large differences in glass surfaces of double silver products, and is also low in cost.
Smart Images

Figure BDA0005103833280000051
Abstract
Description
Technical Field
[0001] The invention belongs to the field of coated glass, and in particular relates to a tempered double-silver LOW-E coated glass and a preparation method thereof. Background Art
[0002] Low-E coated glass refers to a layer of metallic silver deposited on the surface of float glass as a functional layer, which reflects near-infrared rays in sunlight and far-infrared rays in the living environment, thereby reducing the glass's absorption and radiation of infrared rays. That's why it's called low-E coated glass. This type of glass can be used for home doors and windows, as well as for glass curtain walls in shopping malls, office buildings, high-end hotels, and other places where it is needed.
[0003] Low-emissivity coated glass currently has single silver, double silver, triple silver, and even quadruple silver glass, but double silver products are widely accepted by the market for their excellent energy-saving performance, optical properties, and lower prices, and are widely used in various types of building curtain walls at home and abroad. Although more energy-saving triple silver glass has been developed, double silver products still occupy more than 80% of the current market and are still the mainstream product.
[0004] However, there is a common problem with double-silver products: the color of the glass surface of double-silver products changes significantly when viewed at different angles. The large color difference leads to poor visual consistency and design limitations, affecting the aesthetics of the building. At the same time, it also fails to meet the designer's expectations and requirements, which has a certain impact on the visual consistency and appearance of high-requirement buildings. Summary of the invention
[0005] The purpose of the present invention is to provide a temperable double-silver LOW-E coated glass and a preparation method thereof.
[0006] In order to achieve the above object, a technical solution adopted by the present invention is:
[0007] A temperable double-silver LOW-E coated glass comprises a glass substrate and a composite layer coated on the glass substrate, wherein the composite layer comprises a first dielectric layer, a first AZO layer, a first functional layer, a first protective layer, a second AZO layer, an intermediate dielectric layer, a third AZO layer, a second functional layer, a second protective layer, a fourth AZO layer, and a second dielectric layer, which are sequentially coated from the inside to the outside of the glass substrate, wherein the intermediate dielectric layer comprises a first layer, a second layer, and a third layer which are sequentially arranged, wherein the first layer is adjacent to the second AZO layer, and the third layer is adjacent to the third AZO layer, wherein the first layer and the third layer are any one or more combinations of ZnO, SiNx, SiNxOy, AZO, TZO, and TiOx, and the second layer is any one or more combinations of NiCr, Cr, Ti, TiN, NiCrNx, and NiCrOx.
[0008] According to some embodiments of the present invention, the first sublayer and the fourth sublayer are any one or more combinations of ZnO, SiNx, and SiNxOy, the second layer is any one or more combinations of NiCr, Cr, Ti, TiN, NiCrNx, and NiCrOx, and the second sublayer and the third sublayer are any one or more combinations of AZO, TZO, and TiOx.
[0009] According to a preferred embodiment of the present invention, the intermediate dielectric layer includes a first sublayer, a second sublayer, a second layer, a third sublayer and a fourth sublayer arranged in sequence, the first sublayer is ZnO, the second sublayer is AZO, the second layer is NiCr, the third sublayer is AZO, and the fourth sublayer is ZnO. The second layer is preferably NiCr and / or Cr. Due to the addition of NiCr and / or Cr in the intermediate dielectric layer, the propagation path of light in the double silver intermediate dielectric layer can be changed.
[0010] According to some implementation aspects of the present invention, the first sub-layer and the fourth sub-layer are made of the same material; and\or, the second sub-layer and the third sub-layer are made of the same material.
[0011] According to some implementation aspects of the present invention, the second sub-layer and the third sub-layer have the same thickness.
[0012] According to some implementation aspects of the present invention, the thickness of the intermediate dielectric layer is 95-140 nm, and the thickness of the second layer is 6-11 nm.
[0013] According to some embodiments of the present invention, the thickness range of the first sublayer is 50-70nm; the thickness range of the second sublayer is 3-7nm; the thickness range of the third layer is 6-11nm; the thickness range of the third sublayer is 3-7nm; the thickness range of the fourth sublayer is 30-50nm.
[0014] According to some implementation aspects of the present invention, the first dielectric layer and the second dielectric layer are any one layer or a combination of multiple layers of SiNx, ZnO, and ZrO.
[0015] According to some implementation aspects of the present invention, the first protective layer and the second protective layer are both NiCr layers.
[0016] According to some implementation aspects of the present invention, the first functional layer and the second functional layer are both silver layers.
[0017] According to some implementation aspects of the present invention, the thickness range of the first dielectric layer is 40 to 60 nm; the thickness range of the first AZO layer is 8 to 12 nm; the thickness range of the first functional layer is 6 to 12 nm; the thickness range of the first protective layer is 1 to 3 nm; the thickness range of the second AZO layer is 6 to 12 nm; the thickness range of the third AZO layer is 6 to 12 nm; the thickness range of the second functional layer is 4 to 10 nm; the thickness range of the second protective layer is 3 to 6 nm; the thickness range of the fourth AZO layer is 6 to 12 nm; and the thickness range of the second dielectric layer is 25 to 70 nm.
[0018] Another technical solution adopted by the present invention is:
[0019] A method for preparing the temperable double-silver LOW-E coated glass comprises:
[0020] (1) using a magnetron sputtering process to deposit a first dielectric layer on a glass substrate, specifically: firstly, a silicon-aluminum target is sputtered and deposited in a nitrogen atmosphere, and then a zinc-aluminum target is sputtered and deposited in an oxygen atmosphere, and the first dielectric layer is a composite layer of SiNx and ZnO with a thickness of 40 to 60 nm;
[0021] (2) using a magnetron sputtering process to deposit a first AZO layer on the first dielectric layer;
[0022] (3) using a magnetron sputtering process to deposit a first functional layer on the first AZO layer, wherein the functional layer is an Ag layer with a thickness of 6 to 12 nm;
[0023] (4) using a magnetron sputtering process to plate a first protective layer on the first functional layer, wherein the first protective layer is a nickel-chromium alloy (NiCr) layer with a thickness of 1 to 3 nm;
[0024] (5) using a magnetron sputtering process to deposit a second AZO layer on the first protective layer, wherein the thickness of the second AZO layer ranges from 6 to 12 nm;
[0025] (6) using a magnetron sputtering process to deposit an intermediate dielectric layer on the second AZO layer, with a total thickness ranging from 95 to 140 nm, wherein the thickness of the second layer ranges from 6 to 11 nm;
[0026] (7) using a magnetron sputtering process to deposit a third AZO layer on the second dielectric layer, wherein the thickness of the third AZO layer is 6 to 12 nm;
[0027] (8) using a magnetron sputtering process to deposit a second functional layer on the third AZO layer, wherein the second functional layer is an Ag layer with a thickness of 4 to 10 nm;
[0028] (9) using a magnetron sputtering process to plate a second protective layer on the second functional layer, wherein the second protective layer is a nickel-chromium alloy (NiCr) layer with a thickness of 3 to 6 nm;
[0029] (10) using a magnetron sputtering process to deposit a fourth AZO layer on the second protective layer, wherein the thickness of the fourth AZO layer is in the range of 6 to 12 nm;
[0030] (11) A second dielectric layer is deposited on the fourth AZO layer by a magnetron sputtering process. The second dielectric layer is a SiNx and ZrO composite layer with a thickness of 25 to 70 nm.
[0031] According to some implementation aspects of the present invention, in step (6), the method for plating the intermediate dielectric layer includes:
[0032] S1. Under the control of medium frequency AC power supply, zinc-aluminum targets are sputtered and deposited in oxygen atmosphere, and the total power of multiple targets is 206kW;
[0033] S2, using magnetron sputtering technology, AZO target is sputtered and deposited in argon atmosphere, and the total target power is 20kW;
[0034] S3, using a planar cathode, NiCr target was deposited in an argon atmosphere under the control of a DC power supply, with a power of 11.39;
[0035] S4, using magnetron sputtering process, AZO target was sputtered and deposited in argon atmosphere, and the total target power was 20kW;
[0036] S5. Under the control of a medium frequency AC power supply, zinc-aluminum targets are sputtered and deposited in an oxygen atmosphere, and the total power of multiple targets is 124 kW.
[0037] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0038] The present invention provides a temperable double-silver LOW-E coated glass and a preparation method thereof. The present invention provides an intermediate medium layer to change the propagation path of light between a first functional layer and a second functional layer, weaken optical interference and refraction effects, and ultimately reduce the color difference of the glass surface when observed at different angles, so that no matter from which angle the building is observed, the color remains basically consistent with the color of the glass facing it, thereby achieving visual consistency. DETAILED DESCRIPTION
[0039] The present invention will be further described below in conjunction with the embodiments.
[0040] Example 1
[0041] A temperable double-silver LOW-E coated glass comprises a glass substrate and a composite layer coated on the glass substrate, wherein the composite layer comprises a first dielectric layer, a first AZO layer, a first functional layer, a first protective layer, a second AZO layer, an intermediate dielectric layer, a third AZO layer, a second functional layer, a second protective layer, a fourth AZO layer, and a second dielectric layer, which are sequentially coated from the inside to the outside of the glass substrate, and the intermediate dielectric layer comprises a first sublayer, a second sublayer, a second layer, a third sublayer, and a fourth sublayer, which are sequentially arranged, wherein the first sublayer is adjacent to the second AZO layer, and the fourth sublayer is adjacent to the third AZO layer.
[0042] Among them, the first dielectric layer is a combination layer of SiNx and ZnO with a thickness of 33.5nm; the thickness of the first AZO layer is 5nm; the first functional layer is a silver layer with a thickness of 6.7nm; the first protective layer is NiCr with a thickness of 2.1nm; the second AZO layer has a thickness of 3.75nm; the first sublayer is ZnO with a thickness of 68.7nm; the second sublayer is AZO with a thickness of 5nm; the second layer is NiCr with a thickness of 8.85nm; the third sublayer is AZO with a thickness of 5nm; the fourth sublayer is ZnO with a thickness of 41.4nm; the third AZO layer has a thickness of 3.75nm; the second functional layer is a silver layer with a thickness of 9.7nm; the second protective layer is a NiCr layer with a thickness of 4.9nm; the fourth AZO layer has a thickness of 3.75nm; the second dielectric layer is a composite layer of SiNx and ZrO, with a thickness of 53.7nm for SiNx and 6.7nm for ZrO.
[0043] Example 2
[0044] A temperable double-silver LOW-E coated glass comprises a glass substrate and a composite layer coated on the glass substrate, wherein the composite layer comprises a first dielectric layer, a first AZO layer, a first functional layer, a first protective layer, a second AZO layer, an intermediate dielectric layer, a third AZO layer, a second functional layer, a second protective layer, a fourth AZO layer, and a second dielectric layer, which are sequentially coated from the inside to the outside of the glass substrate, and the intermediate dielectric layer comprises a first sublayer, a second sublayer, a second layer, a third sublayer, and a fourth sublayer, which are sequentially arranged.
[0045] Among them, the first dielectric layer is a composite layer of SiNx and ZnO with a thickness of 33.5nm; the thickness of the first AZO layer is 5nm; the first functional layer is a silver layer with a thickness of 6.7nm; the first protective layer is NiCr with a thickness of 2.1nm; the second AZO layer has a thickness of 3.75nm; the first sublayer is ZnO with a thickness of 68.7nm; the second sublayer is AZO with a thickness of 5nm; the second layer is TiN with a thickness of 8.85nm; the third sublayer is AZO with a thickness of 5nm; the fourth sublayer is ZnO with a thickness of 41.4nm; the third AZO layer has a thickness of 3.75nm; the second functional layer is a silver layer with a thickness of 9.7nm; the second protective layer is a NiCr layer with a thickness of 4.9nm; the fourth AZO layer has a thickness of 3.75nm; the second dielectric layer is a composite layer of SiNx and ZrO, with a SiNx thickness of 53.7nm and a ZrO thickness of 6.7nm.
[0046] Example 3
[0047] A temperable double-silver LOW-E coated glass comprises a glass substrate and a composite layer coated on the glass substrate, wherein the composite layer comprises a first dielectric layer, a first AZO layer, a first functional layer, a first protective layer, a second AZO layer, an intermediate dielectric layer, a third AZO layer, a second functional layer, a second protective layer, a fourth AZO layer, and a second dielectric layer, which are sequentially coated from the inside to the outside of the glass substrate, wherein the intermediate dielectric layer comprises a first layer, a second layer, and a third layer, wherein the first layer and the third layer are both ZnO layers, and the second layer is a NiCr layer.
[0048] Among them, the first dielectric layer is a composite layer of SiNx and ZnO with a thickness of 33.5nm; the thickness of the first AZO layer is 5nm; the first functional layer is a silver layer with a thickness of 6.7nm; the first protective layer is NiCr with a thickness of 2.1nm; the second AZO layer has a thickness of 3.75nm; the first layer is ZnO with a thickness of 73.7nm; the second layer is NiCr with a thickness of 8.85nm; the third layer is ZnO with a thickness of 46.4nm; the second functional layer is a silver layer with a thickness of 9.7nm; the second protective layer is a NiCr layer with a thickness of 4.9nm; the fourth AZO layer has a thickness of 3.75nm; the second dielectric layer is a composite layer of SiNx and ZrO, the thickness of SiNx is 53.7nm, and the thickness of ZrO is 6.7nm.
[0049] Comparative Example
[0050] The difference from Example 1 is that the intermediate dielectric layer is only a NiCr layer.
[0051] The temperable double-silver LOW-E coated glass of Examples 1-3 and Comparative Example was tested, and a 6 mm glass substrate was selected. The test results are shown in Table 1:
[0052] Table 1 Colors of tempered double silver LOW-E coated glass before and after tempering in Examples 1-3 and Comparative Example
[0053]
[0054] As can be seen from Table 1, for Example 1, after tempering, the values of a*g and a*c are close, and the values of b*g and b*c are close, and it can be seen that there is no obvious difference in the color of the glass at different angles on the front side (a*g and b*g are when people are facing the glass surface, that is, the human perspective is perpendicular to the glass surface; a*c and b*c indicate that there is an inclined angle between the human perspective and the glass surface, such as 30°, 45°, and 60°). In the comparative example, after tempering, the values of a*g and a*c differ greatly, and the values of b*g and b*c differ greatly (-15.58 and 16.58), and the color of the glass surface at different angles differs greatly.
[0055] In Examples 1-3, the intermediate dielectric layer is ZnO+AZO / TZO / TiOx+NiCr / Cr+AZO / TZO / TiOx+ZnO, wherein AZO / TZO / TiOx represents a combination of one or more of AZO, TZO, and TiOx, and the second layer of the intermediate dielectric layer is a NiCr / Cr layer (one or two of NiCr and Cr). The addition of NiCr / Cr changes the propagation path of light in the intermediate dielectric layer. Since the film layer structures before and after NiCr / Cr are close, the optical interference and refraction effects can be weakened, thereby ultimately reducing the difference in the glass surface viewed from different angles.
[0056] The glass surface in this application refers to the side of the glass located outdoors, and the tester is outdoors to conduct the test.
[0057] Example 4
[0058] The method for preparing the temperable double-silver LOW-E coated glass of Example 1 comprises:
[0059] (1) A first dielectric layer is deposited on a glass substrate by a magnetron sputtering process. The first dielectric layer is a composite layer of SiNx and ZnO. The preparation method is as follows: first, under the control of a medium frequency AC power supply, a silicon aluminum target is sputtered and deposited in a nitrogen atmosphere at a power of 134 kW, and the thickness of the deposited film is 33.5 nm; then, a zinc aluminum target is sputtered and deposited in an oxygen atmosphere at a power of 45 kW, and the thickness of the deposited film is 15 nm;
[0060] (2) using a magnetron sputtering process to deposit a first AZO layer on the first dielectric layer, with a power of 14.9 kW and a deposited film thickness of 5 nm;
[0061] (3) using a magnetron sputtering process to deposit a first functional layer on the first AZO layer: using a planar cathode, under the control of a DC power supply, a silver target was sputtered in an argon atmosphere with a power of 14.9 kW and a deposited film thickness of 6.7 nm;
[0062] (4) using a magnetron sputtering process to deposit a first protective layer on the first functional layer: using a planar cathode, under the control of a DC power supply, a NiCr target was sputtered and deposited in an argon atmosphere with a power of 2.7 kW and a deposited film thickness of 2.1 nm;
[0063] (5) Using magnetron sputtering technology, a second AZO layer is deposited on the first protective layer: the power is 15 kW, and the thickness of the deposited film is 3.75 nm;
[0064] (6) Using a magnetron sputtering process, an intermediate dielectric layer is plated on the second AZO layer in the following order, and the preparation method is:
[0065] S1. Under the control of medium frequency AC power supply, zinc-aluminum targets were sputtered and deposited in oxygen atmosphere. The total power of multiple targets was 206kW, and the thickness of the deposited film was 68.7nm.
[0066] S2, using magnetron sputtering technology, AZO target is sputtered and deposited in argon atmosphere, the total target power is 20kW, and the deposited film thickness is 5nm;
[0067] S3, using a planar cathode, under the control of a DC power supply, the NiCr target is deposited in an argon atmosphere, the power is 11.39, and the thickness of the deposited film is: 8.85nm;
[0068] S4, using magnetron sputtering technology, AZO target is sputtered and deposited in argon atmosphere, the total target power is 20kW, and the deposited film thickness is 5nm;
[0069] S5. Under the control of medium frequency AC power supply, zinc-aluminum targets were sputtered and deposited in oxygen atmosphere. The total power of multiple targets was 124 kW, and the thickness of the deposited film was 41.4 nm.
[0070] (7) Using a magnetron sputtering process, a third AZO layer is deposited on the second dielectric layer: the power is 15 kW, and the thickness of the deposited film is 3.75 nm;
[0071] (8) Using magnetron sputtering technology, the second functional layer is deposited on the third AZO layer: using a planar cathode, under the control of a DC power supply, a silver target is sputtered in an argon atmosphere with a power of 11 kW and a deposited film thickness of 9.7 nm;
[0072] (9) using a magnetron sputtering process to deposit a second protective layer on the second functional layer: using a planar cathode, under the control of a DC power supply, a NiCr target was sputtered and deposited in an argon atmosphere with a power of 5.9 kW and a deposited film thickness of 4.9 nm;
[0073] (10) Using a magnetron sputtering process, a fourth AZO layer is deposited on the second protective layer: the power is 15 kW, and the thickness of the deposited film is 3.75 nm;
[0074] (11) A second dielectric layer was deposited on the fourth AZO layer by using a magnetron sputtering process: under the control of a medium frequency AC power supply, a silicon aluminum target was sputtered and deposited in a nitrogen atmosphere, with a total power of 215 kW for multiple targets and a deposited film thickness of 53.7 nm; a Zr target was sputtered and deposited in an oxygen atmosphere with a total power of 27 kW and a deposited film thickness of 6.7 nm.
[0075] The advantages of the tempered double-silver LOW-E coated glass in this example are: setting the second layer changes the propagation path of light between the first functional layer and the second functional layer, and the first layer and the third layer before and after the second layer form a symmetrical structure, which can weaken the effect of optical interference and refraction, and ultimately reduce the color difference of the glass surface at different angles. Whether observing from the front or side of the glass surface, visual consistency can be maintained, solving the problem of large color differences on the glass surface of double-silver products; the cost is low.
[0076] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A temperable double silver LOW-E coated glass, characterized in that: The invention comprises a glass substrate and a composite layer plated on the glass substrate, wherein the composite layer comprises a first dielectric layer, a first AZO layer, a first functional layer, a first protective layer, a second AZO layer, an intermediate dielectric layer, a third AZO layer, a second functional layer, a second protective layer, a fourth AZO layer, and a second dielectric layer which are plated in sequence from the inside to the outside of the glass substrate, wherein the intermediate dielectric layer comprises a first layer, a second layer, and a third layer which are arranged in sequence, wherein the first layer and the third layer are any one or more combinations of ZnO, SiNx, SiNxOy, AZO, TZO, and TiOx, and the second layer is any one or more combinations of NiCr, Cr, Ti, TiN, NiCrNx, and NiCrOx.
2. The temperable double silver LOW-E coated glass according to claim 1, characterized in that: The first layer includes a first sublayer and a second sublayer, the third layer includes a third sublayer and a fourth sublayer, the first sublayer and the fourth sublayer are both a combination of any one or more of ZnO, SiNx, and SiNxOy, and the second sublayer and the third sublayer are both a combination of any one or more of AZO, TZO, and TiOx.
3. The temperable double silver LOW-E coated glass according to claim 2, characterized in that: The first sub-layer is made of the same material as the fourth sub-layer; and\or, the second sub-layer is made of the same material as the third sub-layer.
4. The temperable double silver LOW-E coated glass according to claim 2, characterized in that: The thickness range of the first sublayer is 50-70nm; the thickness range of the second sublayer is 3-7nm; the thickness range of the third layer is 6-11nm; the thickness range of the third sublayer is 3-7nm; the thickness range of the fourth sublayer is 30-50nm.
5. The temperable double silver LOW-E coated glass according to claim 1, characterized in that: The thickness of the intermediate dielectric layer is 95-140 nm, wherein the thickness of the second layer is 6-11 nm.
6. The temperable double silver LOW-E coated glass according to claim 1, characterized in that: The first dielectric layer and the second dielectric layer are any one layer or a combination of multiple layers of SiNx, ZnO, and ZrO; the first protective layer and the second protective layer are NiCr layers.
7. The temperable double silver LOW-E coated glass according to claim 1, characterized in that: The first functional layer and the second functional layer are both silver layers.
8. The temperable double silver LOW-E coated glass according to claim 1, characterized in that: The thickness range of the first dielectric layer is 40 to 60 nm; the thickness range of the first AZO layer is 8 to 12 nm; the thickness range of the first functional layer is 6 to 12 nm; the thickness range of the first protective layer is 1 to 3 nm; the thickness range of the second AZO layer is 6 to 12 nm; the thickness range of the third AZO layer is 6 to 12 nm; the thickness range of the second functional layer is 4 to 10 nm; the thickness range of the second protective layer is 3 to 6 nm; the thickness range of the fourth AZO layer is 6 to 12 nm; and the thickness range of the second dielectric layer is 25 to 70 nm.
9. A method for preparing the temperable double-silver LOW-E coated glass according to any one of claims 1 to 8, characterized in that: include: (1) using a magnetron sputtering process to plate a first dielectric layer on a glass substrate; (2) using a magnetron sputtering process to deposit a first AZO layer on the first dielectric layer; (3) using a magnetron sputtering process to deposit a first functional layer on the first AZO layer; (4) using a magnetron sputtering process to plate a first protective layer on the first functional layer; (5) using a magnetron sputtering process to deposit a second AZO layer on the first protective layer; (6) using a magnetron sputtering process to plate an intermediate dielectric layer on the second AZO layer; (7) using a magnetron sputtering process to deposit a third AZO layer on the second dielectric layer; (8) using a magnetron sputtering process to deposit a second functional layer on the third AZO layer; (9) using a magnetron sputtering process to plate a second protective layer on the second functional layer; (10) using a magnetron sputtering process to deposit a fourth AZO layer on the second protective layer; (11) A second dielectric layer is deposited on the fourth AZO layer by a magnetron sputtering process.
10. The method for preparing the temperable double-silver LOW-E coated glass according to claim 9, characterized in that: In step (6), the method for plating the intermediate dielectric layer includes: S1, sputtering deposition of zinc-aluminum target in oxygen atmosphere; S2, AZO target was sputtered and deposited in argon atmosphere; S3, NiCr target was deposited in argon atmosphere; S4, AZO target was sputtered and deposited in argon atmosphere; S5. Zinc-aluminum target is sputtered and deposited in an oxygen atmosphere.
Citation Information
Patent Citations
Low-emissivity coated glass and manufacturing method thereof
CN103144379A
Middle-transmission low-reflection temperable double-silver low-emissivity coated glass
CN114213037A
Low-emissivity coated glass without chromatic aberration on glass film surface
CN209276384U
Neutral-color temperable double-silver LOW-E coated glass
CN220812226U